(untitled) (Journal of Bangladesh Academy of Sciences, 2026)
Deterioration of groundwater (GW) quality due to natural and anthropogenic activities remains a critical concern in the Dhaka-Narayanganj city of Bangladesh because it is the primary drinking water (DW) source for millions of slum dwellers, and comprehensive health risk assessments integrating advanced pollution indices (PIs) and Carcinogenic Risk (CR) evaluation remain limited. Here, GW quality with heavy metal (HM) contamination and associated human health risks were assessed in 23 slum areas across the Dhaka-Narayanganj city by measuring physicochemical parameters along with concentration of nutrients and HMs. Furthermore, the Canadian Council of Ministers of the Environment Water Quality Index (CCME-WQI) and multiple PIs based on the obtained concentration of HMs were evaluated. Most of the physicochemical parameters and concentration of nutrients were within the World Health Organization (WHO) limit of DW, and the order of nutrient levels was nitrate ˃ phosphate ˃ ammonia. Among all HMs, Fe was the principal aesthetic concern (176 - 470 μg/L), with 4 stations exceeding the limit of WHO (300 μg/L) and As, Cr, Hg, Mn, and Pb being below health-concern limits. PIs classified 87 % of stations as low contamination, while CCME-WQI categorized 82.6 % as "good," 13 % as "excellent," and one as "fair." However, CR assessment identified that 5 stations (21.7 %) in Narayanganj and Shiddhirganj industrial areas pose “unacceptable” lifetime CR (>1×10⁻⁴) due to continuous ingestion and dermal contact with As-contaminated GW over many years. Standard water quality indices underestimate chronic health risks, so carcinogenic assessments must be added to regular GW monitoring to protect vulnerable slum communities. J. Bangladesh Acad. Sci.50(2); 283–298: June 2026